2014
DOI: 10.5455/njppp.2014.4.060520141
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of short duration of slow deep breathing on heart rate variability in healthy adults

Abstract: Background: Various types of breathing exercises have various effects on autonomic nervous system like fast breathing increases sympathetic tone and slow breathing increases parasympathetic tone. But these changes are seen when those exercises are done for long duration. Heart rate variability (HRV) reveals the autonomic status very effectively. So took up the study to know the effects of short duration (5 min) of slow deep breathing on heart rate variability Aims & Objective: To study the HRV Before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…RMSSD, which is the principal time domain of HRV, reflects the parasympathetic activity and is associated with high‐frequency power (Shaffer and Ginsberg, 2017). Our results are consistent with the findings of a study by Chinagudi et al (2014), who reported that after slow and deep breathing at 6 breaths/min (inhale:exhale = 1:1), RMSSD decreased (not significant). As the participants were experiencing slow deep breathing exercises for the first time, their sympathetic system's fight‐or‐flight response may have been activated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…RMSSD, which is the principal time domain of HRV, reflects the parasympathetic activity and is associated with high‐frequency power (Shaffer and Ginsberg, 2017). Our results are consistent with the findings of a study by Chinagudi et al (2014), who reported that after slow and deep breathing at 6 breaths/min (inhale:exhale = 1:1), RMSSD decreased (not significant). As the participants were experiencing slow deep breathing exercises for the first time, their sympathetic system's fight‐or‐flight response may have been activated.…”
Section: Discussionsupporting
confidence: 93%
“…These data could confirm that slow breathing control enhances parasympathetic activity and lowers BP. However, Chinagudi et al (2014) demonstrated that in healthy adults with sympathetic predominance, high‐frequency power in normalized units significantly decreased, whereas low‐frequency power in normalized units and low‐ to high‐frequency ratio significantly increased after slow and deep breathing at 6 breaths/min for 5 min. However, in their study, the inhale/exhale ratio was 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the exercise was done regularly for long duration, slowly sympathetic system tone decreased and parasympathetic tone increased. [13] HRV increases as parasympathetic effect increases until it reaches a plateau level. Beyond this level, HRV actually decreases with further increases in parasympathetic effect.…”
Section: Breath Cyclementioning
confidence: 97%
“…Specifically, the breathing rate of six breaths per minute (0.1 Hz), also known as resonance breathing, is considered to be optimal to increase baroreceptor activity and heart rate variability (HRV), which are associated with increased resilience and higher positive affect (Lehrer & Gevirtz, 2014; Mather & Thayer, 2018; Van Diest et al., 2014). It has been found that even a brief engagement in SDB can lead to increased baroreceptor activity and HRV (Chinagudi et al., 2014; Courtois et al., 2020; Gholamrezaei et al., 2019), decreased effects of painful stimulation (Chalaye et al., 2009), and increased lung capacity (Shravya et al., 2013). Importantly, the neural effects have also been investigated, finding resonant slow cortical potentials at 0.1 Hz (Hinterberger et al., 2019), as well as globally heightened spontaneous alpha activity already after a few minutes of SDB (Cheng et al., 2018; Fumoto et al., 2004; Komori, 2018; Yu et al., 2011).…”
Section: Neural Oscillations As Related To Breathingmentioning
confidence: 99%